2013 IEEE Business Engineering and Industrial Applications Colloquium (BEIAC) 2013
DOI: 10.1109/beiac.2013.6560161
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of treated Kenaf (Hibiscus cannabinus) polyester composite at different alkaline concentration

Abstract: Increase of awareness among people has increased the demand for green products. Other synthetic materials such as plastic and fibreglass has been reduced because of the environmental concern. Reinforcement with other green materials such as lignocellulosic materials has been done to reduce the dependency on synthetic material. Kenaf (Hibiscus cannabinus L.) fibres have the biggest potential to be used as a composite product and also as reinforcement in the composite products. Lignocellulosic materials includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…This treatment is an essential stage in natural fibers in order to remove the hemicellulose, lignin and wax from the outer surface of the kenaf fibers, which enhances the interfacial bonding between the kenaf and the polymer matrix. This is supported by the research results of Masitah et al who stated that the surface of alkali-treated fiber has no impurities and this alkali solution increased the mechanical bonding between the fiber and matrix polymer [ 37 ].…”
Section: Resultsmentioning
confidence: 58%
“…This treatment is an essential stage in natural fibers in order to remove the hemicellulose, lignin and wax from the outer surface of the kenaf fibers, which enhances the interfacial bonding between the kenaf and the polymer matrix. This is supported by the research results of Masitah et al who stated that the surface of alkali-treated fiber has no impurities and this alkali solution increased the mechanical bonding between the fiber and matrix polymer [ 37 ].…”
Section: Resultsmentioning
confidence: 58%
“…However, based on the study by Kassim et al, 98 the highest flexural strength and modulus values of the polyester composites were achieved when the kenaf fibers treated with 3% NaOH solution and higher NaOH concentration resulted in reduced mechanical properties. Interestingly, Hamzah et al 99 reported that the alkaline treatment of long kenaf fibers using only 1% NaOH enhanced the tensile strength and modulus of polyester composites compared to untreated kenaf fiber composites.…”
Section: Properties Of the Composites Produced Using Treated Kenaf Fibermentioning
confidence: 95%